A Chemoenzymatic Formal Synthesis of Epoxyquinols A and B - Collins, Jonathan A.; Gerry, Christopher J.; Duncan, Madeleine M. (Synlett, 2019)
A formal synthesis of epoxyquinols A and B was completed in nine steps starting from benzoic acid. Enantioselectivity was established through an enzymatic arene dihydroxylation reaction performed by whole cells of Ralstonia eutropha B9 expressing benzoate dioxygenase. Subsequent formation of the enone core was facilitated by a Dauben–Michno-type oxidative transposition of an allylic tertiary alcohol.
Keywords: Ralstonia eutropha; benzoate dioxygenase; chemoenzymatic synthesis; biocatalysis; asymmetric synthesis; epoxyquinoids